Effects of Arm Swing Exercise Program on HbA1c and Nutritional Status in Adults with Type 2 Diabetes in Community - Wanna, Jenjira; Terathongkum, Sangthong; Thipsuwannakool, Varaporn (The Bangkok Medical Journal, 2018)
OBJECTIVE: This experimental research design randomized two groups pre- andpost- test, aimed at examining the effects of arm swing exercise program on hemoglobinA1c (HbA1c) and nutritional status in adults with type 2 diabetes mellitus (T2DM) MATERIAL AND METHODS: Participants from Sub-district Health PromotingHospital were randomly divided into two groups: an experimental group with 22participants receiving arm swing exercise program for 12 weeks and a control groupwith 21 participants receiving routine nursing care. Data collection was done beforeand after the intervention using a demographic and a perceived self-efficacy in exercisequestionnaire, HbA1c, waist circumference and body mass index (BMI). The data wereanalyzed by using descriptive statistics, Paired t-test and Independent t-test. RESULTS: The findings showed that after the arm swing exercise program, theexperimental group had significantly lower average of HbA1c, waist circumference andBMI compared with before the program (p = 0.010, p = 0.000, p = 0.003, respectively).The experimental group also had lower average of HbA1c compared with the controlgroup (p = 0.013), but waist circumference and BMI were not significant. CONCLUSION: The arm swing exercise program should be applied to adults withT2DM to control diabetes and its complications.